Criteria and indicators of quality assessment of future professionals training in the system of Ukrainian higher education - Boyko, Mariia (Journal of Education, Health and Sport, 2019)
The article presents the analysis of the main approaches to the assessment of the quality of education and the factors that influence the process of its provision in modern higher education institutions. The investigation outlines the peculiarities of the criteria for quality assessment of higher education. These criteria give freedom for universities to form educational programs and curricula; provide continuous monitoring and review educational programs in order to improve their quality, stimulate the introduction of innovations in educational standards. The determinants of effectiveness in quality assurance at higher education institutions have been determined and the indicators by which it can be objectively evaluated have been discussed.